Acceptance of social service robots in the hotel industry - Yves Staudt; Jan Mosedale; Saphir Ben Dakon (Marketing Review St.Gallen, 2024)
In recent years, the utilization of robots has increased significantly. To the best of our knowledge, all papers have analyzed the acceptance of robots in terms of their functionalities. None of the papers have focused on creating personas based on findings regarding attitudes towards service robots. To determine the acceptability of social service robots in the hotel industry, a structured online survey of hotel guests was conducted, resulting in two clusters of positive and neutral attitudes towards robots in general and positive and negative attitudes towards social service robots in hotels. While demographic attributes were not found to influence acceptance, key attributes were the general attitude towards robots, previous use of robots, and the fear of competition with humans. Using the derived personas, hotel managers can develop a tailored strategy.
Keywords: 650